APLIKASI KOMPOS KULIT BUAH JARAK PAGAR SEBAGAI SUMBER KALIUM PADA BUDIDAYA TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) - Bagus Arrasyid (FP AGRO 16 UMY 028, 2016)
A research entitling “Application of compost rind jatropha as a source of potassium in the sweet corn (Zea mays saccharata Sturt) cultivation " was conducted in the Research Laboratory, Soil Laboratory and Field trials Faculty of Agriculture, Universitas Muhammadiyah Yogyakarta from October 2015 to March 2016. The Research aims to study the influence of compost rind Jatropha in the sweet corn (Zea mays saccharata Sturt) cultivation and get a proper dose of compost rind jatropha in increasing the growth and yield of sweet corn (Zea mays saccharata Sturt). This research conducted using an experimental method with single factor that is arranged in a completely randomized design. The treatments dose tested ie compost rind jatropha (KJP), which consists of four levels, namely, 250 kg KCl / hectare + 0 KJP kg / hectare, 125 kg KCl / hectare + KJP 273.89 kg / hectare, 62.5 kg KCl / hectare + KJP 410.84 kg / hectare, 0 kg KCl / hectare + KJP 547.79 kg / hectare. Each treatment repeated 3 times so that there are 12 experimental units, each unit consisting of three plants trial so that there are 36 plants. All treatment was given at a dose of manure 20 ton / hectare, Urea 400 kg / hectare given 2 times, SP-36 300 kg / hectare.